Teror bom Azahari-Noor Din - Abimanyu, Bambang, 1953-; Indonesia (Jati Padang, Jakarta : Penerbit Republika, 2006)
Law enforcement on bombing and terror cases in Indonesia
References : p. 191
Keywords: Terrorism -- Indonesia; Bombings -- Indonesia; Law enforcement -- Indonesia